Bahasa Inggris - Aqila Mufida Safitri; Ani Agus Puspawati (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2026)
This study aims to analyze the role of smart tourism in enhancing the competitiveness and sustainability of tourism destinations in Indonesia's digital era. Employing a Systematic Literature Review (SLR) approach based on the Kitchenham (2004) framework and PRISMA guidelines, this research systematically identified, screened, and analyzed 35 final articles sourced from Google Scholar via the Harzing Publish or Perish (PoP) application, covering publications from 2021 to 2026. The findings reveal that smart tourism implementation in Indonesia encompasses three primary dimensions: digital technology and infrastructure, destination governance, and tourist experience. AI and WebGIS technologies dominate implementation (33%), followed by application digitalization (28%), e-tourism and social media (22%), and IoT-based support systems (17%). The main inhibiting factors include uneven digital infrastructure, low digital literacy among tourism actors, and fragmented regulation and coordination. Conversely, the supporting factors consist of government policy, technological development, stakeholder collaboration, and digital innovation by start-ups. Overall, smart tourism plays a strategic role in realizing inclusive and sustainable tourism in Indonesia, with its success contingent upon synergistic efforts to overcome barriers and optimize enabling factors toward the vision of Indonesia Emas 2045.